Bleich ou o paradoxo da tradução - Gilles Jean Abes (Cadernos de Tradução, 2009)
This article is based on a comparative study of Charles Baudelaire’s Flowers of Evil (Les fleurs du mal) for the portuguese language, with special regard to Jamil Almansur Haddad and Ivan Junqueira’s versions. At first, we focused on the poem Hair (La chevelure) trying to observe how the translator’s approach can whether enrich or impoverish the work due to “deformations” imposed to the source text that come from several restrictions. In the literary text, those traces are particularly visible, creating a paradoxical setting for the translation. This paradox becomes stronger as we look closely to the expression “counterfeit money” which Carlos Drummond de Andrade employed thinking through translation. This “conviction” emerged from the very difficulty of the translating process. Thus, all counterfeit currencies – Derrida, Baudelaire, and Drummond’s, come together and, from that conviction, this concept unroll in several directions: should we understand this “counterfeit money” as a mere fraud? Considering this fact and this point of view, wouldn’t we underestimate the power of the translated text? It is necessary to look at a translation and analyse it in terms of dissonance. Dissonance as a divergence asking for another translation, turning this “fake piece” into a machine which causes events.